Determinant Factors Of The Stock Return In Manufacturing Companies Listed In The Indonesian Stock Exchange In The Period Of 2013 - 2015 - Rendy Lee (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to investigate the effects of Earnings per Share, Price Earnings Ratio, and Debt to Equity Ratio, both partially and simultaneously, on the Stock Return of manufacturing companies listed in the Indonesian Stock Exchange. The period of the study was 2013 - 2015. This was an associative study aiming to investigate the effects or relationships of two or more variables. The research sample, consisting of 35 companies, was selected by means of the purposive sampling technique with the research period of 2013 - 2015.  The data analysis technique to answer the research problems was the panel data regression analysis technique using the program of EViews. The results of the study showed that EPS had a significant positive effect on the stock return; this was indicated by the value of t statistics of 2,928136 and a significance value of 0.0074. PER did not have a significant positive effect on the stock return; this was indicated by the value of t statistics of 0,095663 and a significance level of 0,9241. DER had a significant negative effect on the stock return; this was indicated by the value of t statistics of – 0.307209 and a significance value of 0,7596.